The beneficial effect of positive treatment expectations on pharmacological migraine prophylaxis. Issue 2 (13th May 2021) - Schmidt, Katharina; Berding, Tobias; Kleine-Borgmann, Julian; Engler, Harald; Holle-Lee, Dagny; Gaul, Charly; Bingel, Ulrike
Abstract : Supplemental Digital Content is Available in the Text. Positive expectations towards pharmacological preventive treatment revealed beneficial effects on its efficacy, especially in more severely affected patients, underscoring their relevance in the treatment context. Abstract: Migraine is one of the leading causes of years lived with disability and considered to be a major global health concern. Pharmacological preventive treatment often causes side effects that limit the adherence to longer-term treatment regimens. Both experimental and clinical evidence suggests that positive expectations can modulate pain and analgesic treatment effects. However, the role of expectations in migraine prophylactic treatment has not systematically been investigated. Here, we examined the influence of treatment expectation before commencing pharmacological preventive treatment on its efficacy and tolerability in N = 134 episodic (30%) and chronic migraine (70%) patients in a prospective, longitudinal observational study over the course of 6 months. The migraine prophylaxis reduced the number of headache and migraine days with acceptable tolerability. Positive treatment expectation was associated with a generally lower number of headache and migraine days and a stronger reduction in headache days over the course of the treatment in chronic but not in episodic migraine patients. Moreover, patients with prior treatment showed a stronger reduction in headache days with higher expectation as compared to patients without prior experience. Our results underscore the relevance of further exploring the role of treatment expectation and its systematic modulation in patients with migraine and other pain conditions.